Misconception Against The Prophet And The Qur'an In Orientalist Literature - Nusairah Binti Ramli (Universiti Sains Islam Malaysia, 2024)
Islam and Muslim becomes the subject interest of western intellects and it can be seen through their writings and efforts to understand this religion. There are many sources found written by these western scholars on Islam and Muslims. However, some of the literatures seem associate with biased and sense of prejudice where Islam projected in a negative way. This may lead to misunderstanding on Islam because it portrayed in unfavourable images that threat modern civilization. This research observes some of the western documentation in order to get general ideas on claim on Islam through the eye of some well-known orientalist and analyse through the writings of Muslims scholar. The researcher found that these allegations made were untrue and miscalculated. The researcher found that the statements could lead to confusion about Islam especially between ignorant Muslim and non-Muslim. They might believe these accusations and act against Islam. Thus, the researcher suggests that Muslim should be more aware on these issues so that they will not become the victims of these propagations. This allegation does not stop but continue in different method, which is online through websites.